A redesigned approach to the additional damping method in the dynamic analysis of simply supported railway bridges. (15th August 2021) - Glatz, Bernhard; Fink, Josef
Highlights: The common Additional Damping Method can lead to non-conservative results. Shortcomings of the common Additional Damping Method are identified and eliminated. A parametric study shows vehicle-bridge interaction effects for four train types. A new approach to additional damping delivers conservative lower bounds. Abstract: In the dynamic analysis of simply supported railway bridges, the choice of vehicle models directly affects the quality of computed results. Simple moving load models usually overestimate the bridge response in comparison with models taking into account vehicle-bridge interaction effects. In order to compensate for this discrepancy, the Eurocode allows the increasing of structural damping for analyses performed with a moving load model. The specified additional damping is based on investigations carried out by the European Rail Research Institute in 1999 and may yield non-conservative results. This paper describes an extensive parametric study inspired by the common Additional Damping Method, aiming to eliminate its identified shortcomings. The applied input parameters for the study are based on existing European simply supported bridge structures with a ballast layer. In order to match the vertical accelerations computed with the Detailed Interaction Model, the additional damping for the Moving Load Model is determined for four European high-speed trains. The results show that the additional damping as integrated in the Eurocode is non-conservative. A redesigned approach enables the definition of conservative additional damping functions depending on the natural bridge frequency, the bridge mass and the train type.